SEMANTIC WEB: flow for publishing open and linked data - Santarém Segundo, José Eduardo (Informação em Pauta, 2018)
Publishing open and semantic data has become a major challenge for organizations around the world. There is a wide variety of actions that must be performed before a data publishing project can be completed. The main objective of this research is to present a phase-oriented organizational flow proposal that describes the activities that should be developed in the process of publication of data in an open and semantic format following the best practices of linked data. The methodology used is based on descriptive and analytical research, based on documentary analysis. As a result, it is expected that the presented flow can contribute to the development of new projects of publication of data in open and semantic format.